Comparison of anthropometric parameters and laboratory test results before and after the COVID-19 outbreak among Chinese children aged 3–18 years - Dong, Wen-Hong; Gu, Tian-Miao; Zhu, Bing-Quan; Shen, Ying; He, Xin-Yu; Bai, Guan-Nan; Shao, Jie (Frontiers in Public Health, 2023)
Objective To compare the physiological health of Chinese children around the COVID-19 lockdown. Methods We extracted data on children's anthropometric and laboratory parameters from May to November in both 2019 and 2020 from the Health Checkup Center, Children's Hospital, Zhejiang University School of Medicine, Hangzhou, China. Overall, 2162 children aged 3~18 years without comorbidities in 2019 and 2646 in 2020 were assessed. Mann Whitney U tests were used to compare differences between the above health indicators before and after COVID-19 outbreak. Quantile regression analyses adjusted for age, sex and body mass index (BMI) were also used in analysis. Chi-square tests and Fisher's exact tests were used for comparing differences of categorical variables. Results Compared with children examined in 2019 before the outbreak, children in 2020 had a higher median z score of BMI for age (−0.16 vs. −0.31), total cholesterol (TC, 4.34 vs. 4.16 mmol/L), low density lipoprotein cholesterol (LDL-C, 2.48 vs. 2.15 mmol/L), high density lipoprotein cholesterol (HDL-C, 1.45 vs. 1.43 mmol/L) and serum uric acid (290 vs. 282 μmol/L), and a lower hemoglobin (Hb, 134 vs. 133 g/L), triglycerides (TG, 0.70 vs. 0.78 mmol/L) and 25(OH)D (45.8 vs. 52.2 nmol/L), all P < 0.05. No differences were identified for waist height ratio, blood pressure and fasting glucose (both P > 0.05). However, in regression models after adjusting, BMI, TC, LDL-C, blood glucose and sUA were positively correlated with year; while Hb, TG and 25(OH)D were negatively correlated with year (all P < 0.05). Accordingly, children in 2020 had a higher prevalence of overweight/obesity (20.6 vs. 16.7%, P < 0.001), hypercholesterol (16.2%vs. 10.2%, P < 0.001), high LDL-C (10 vs. 2.9%, P < 0.001), hyperuricemia (18.9 vs.15.1%, P = 0.002), vitamin D deficiency (22.6 vs. 8.1%, P < 0.001) and a lower prevalence of high TG (4.3 vs. 2.8%, P = 0.018) compared with children in 2019. Conclusion In this real-world study, we found that long-term lockdown due to COVID-19 outbreak might cause adverse impact on children's metabolic health, which might increase their future risk of cardiovascular diseases. Thus, parents, health professionals, educationists, and caregivers should pay more attention to children's dietary pattern and lifestyle, especially in this new normal against COVID-19.